Website-Based Integrated One-Stop Service System of the Ministry of Religious Affairs Office Jayapura Regency Using Rational Unified Process - Lolombulan, Chaelsie Ribka; Titaley, Jullia; Alfonsius, Eric (Universitas Teknokrat Indonesia, 2025)
The public service management system at the Ministry of Religious Affairs Office, Jayapura Regency, remains reliant on manual processes, resulting in inefficiencies such as prolonged processing times, data redundancy, and challenges in tracking service requests. This study aims to design and develop a web-based Integrated One-Stop Service (IOSS) system to enhance service efficiency, accuracy, and accessibility. The Rational Unified Process (RUP) methodology was employed as the system development framework due to its structured, iterative, and flexible approach to managing the software development lifecycle. The design phase commenced with a needs analysis conducted through in-depth interviews with employees and service users to identify system requirements and existing challenges. The system design encompassed the development of an intuitive user interface prototype and a comprehensive database to support IOSS operations. System evaluation through black box and usability testing methods yielded a 100% functionality success rate and a user satisfaction score of 4.46 on a scale of 1 to 5, indicating that the system operates effectively. The findings demonstrate that the developed system significantly improves public accessibility and satisfaction with government services. This study contributes to the advancement of public service digitalization, fostering a more efficient and responsive service delivery system.